2010
DOI: 10.1159/000295775
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Dependent Changes in Connective Tissue Remodeling: Physiological Differences in Circulating MMP-3, MMP-10, TIMP-1 and TIMP-2 Level

Abstract: Background: The mechanisms which cause age-dependent remodeling of connective tissue are still not fully understood. Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) constitute an important proteolytic pathway affecting physiological matrix remodeling. Objective: The way in which changes in the extracellular matrix metabolism during the ageing process influence the level of circulating MMP-3 and MMP-10, as well as their tissue inhibitors TIMP-1 and TIMP-2, in a healthy popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 53 publications
5
28
3
4
Order By: Relevance
“…Because serum levels of MMP-10 in human seemed to be less than 0.5 ng/mL, as previously reported [20].…”
Section: Effects Of Mmp-10 On the Phosphorylation Of Smads And Bmp-insupporting
confidence: 61%
“…Because serum levels of MMP-10 in human seemed to be less than 0.5 ng/mL, as previously reported [20].…”
Section: Effects Of Mmp-10 On the Phosphorylation Of Smads And Bmp-insupporting
confidence: 61%
“…If MMP-3 is an independent cause of macroprolactinaemia, the effect of elevated MMP-3 levels should be added to that of ageing, resulting in a higher prevalence of macroprolactinaemia in RA patients than in the age-matched control subjects. Serum MMP-3 levels in the elderly control subjects were found to be higher than those in the young control subjects, in accordance with the previous report that serum MMP-3 values were positively correlated with age (16). Some unknown factor operating upstream of MMP-3 and ageing may be involved in the pathogenesis of macroprolactinaemia.…”
Section: Discussionsupporting
confidence: 90%
“…In this study serum MMP-3 concentration was higher in females compared to males. Komosinska-vassevk et al found different MMP-3 serum level in males and females (Komosinska-Vassev et al, 2011). These findings show the necessity of matching age and sex for analysis of MMP-3 in the pathological conditions.…”
Section: Resultsmentioning
confidence: 95%